Sciatica due to Schwannoma at the Sciatic Notch - Yavuz Haspolat; Feyza Unlu Ozkan; Ismail Turkmen; Bahattin Kemah; Yalcin Turhan; Serhan Sarar; Korhan Ozkan (Case Reports in Orthopedics)
Schwannomas are rarely seen on the sciatic nerve and can cause sciatica. In this case report we aimed to present an unusual location of schwannoma along sciatic nerve that causes sciatica. A 60-years-old-man was admitted to us with complaints of pain on his thigh and paresthesia on his foot. Radiography of the patient revealed a solitary lesion on the sciatic nerve. The lesion was excised and the symptoms resolved after surgery.